Erosi Demokrasi: Memikirkan Ulang Keberadaan Oligarki dalam Melorotnya Perwujudan Demokrasi di Kolombia Pasca-Perang Saudara hingga 2022 - Christian, Jonathan Kay; Anastasya Jesslyn Hartono Salim; Keisya Diva Kurniawan (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
Nowadays, the democratization process is often hampered not by power struggles, but by the presence of 'invisible hands' (certain organizations, elites, and groups) that penetrate the government structure and disrupt the circulation of democratization in a country. This case occurred in the Colombian government, where there is a specific pattern of nonstate social order - companies, political elites, mafia, and so on - that influences the government structure of a country, and plays the role of power behind the official government. This causes an issue that affects the lives of the Colombian people and government, namely the existence of mafia elites who infiltrate various aspects of society, including the law and government of Colombia itself. The research method used is qualitative descriptive based on data collection through books, journals, articles, and other reliable sources. This paper aims to explain how the presence of mafia elites in Colombia affects the country's democracy and civil society life using Robert Michels' Iron Law of Oligarchy theory. The results of the study show that the existence of drug cartels uses power to make unilateral decisions by taking actions that ignore the official government and the voices of civil society, the dominance of elites and criminals by launching violence and repression for their own interests, and the apathy of the Colombian people towards the existing government system, seen from their indifference to the leaders elected during the election. Keywords: democracy, elite, oligarchy, iron law of oligarchy, mafia, Colombia